Improving Male Partner Involvement in HIV-Positive Women's Care Through Behavioral Change Interventions in Malawi (WeMen Study): A Prospective, Controlled Before-and-After Study - Triulzi, Isotta; Ciccacci, Fausto; Palla, Ilaria; Mthiko, Bryan; Thole, Darlington; Marazzi, Maria Cristina; Palombi, Leonardo; Turchetti, Giuseppe; Orlando, Stefano (Frontiers in Public Health, 2022)
Several strategies and interventions have been implemented to improve male partner involvement (MI) in Sub-Saharan Africa, but evidence on successful interventions is scarce. This controlled before-and-after intervention study aims to evaluate the impact of three interventions on male partners' involvement in HIV+ women's care in Malawi. We piloted these three interventions: the organisation of a special day for men, the deployment of male champions in communities to increase awareness on MI, and the delivery of an incentive (food package) for couples attending the facility. We observed a significant increase in the number of women accompanied by their partners (from 48.5% to 81.4%) and the number of women feeling safe at home (from 63.5% to 95.2%) after the special day intervention. This outcome increased after the deployment of male champions in communities (from 44.0% to 75.0%). No significant improvement was observed in the site where we delivered the incentive to couples. Our findings showed that the special day for men and the use of male champions might effectively increase the male involvement in the health of their female partners.